Exploring the Nexus between People, Physical Evidence, Satisfaction, and Loyalty in Healthcare Services - Wasito, Wasito; Gunawan, Kristin Natalia; Baihaqi, Muhammad Iqbal (JURISMA : Jurnal Riset Bisnis & Manajemen, 2024)
This study offers a comprehensive approach to exploring factors influencing patient satisfaction and loyalty in hospitals. By focusing On Santosa Hospital Bandung Central's Inpatient Installation. This study provides distinctive and contextual insights into the role of human resources and physical evidence in determining patient perception and behavior. Unlike previous studies that focused on common factors, this study delves deeply into how the interaction between aspects of human services and the physical environment contributes to patient satisfaction and, ultimately, affects their loyalty to the hospital. The research method used is Verification Analysis. Data collection using questionnaires, and sampling techniques using consecutive sampling with respondents taken by 100 patients. Data collection in the field was carried out in 2023—data analysis techniques using the Path Analysis. The results showed that people and physical evidence simultaneously affected patient satisfaction. Furthermore, the effect of physical evidence on patient satisfaction both directly and indirectly indicates that the better the physical evidence seen by patients, the more patient satisfaction will increase, while people and physical evidence together affect loyalty, and satisfaction influences patient loyalty at Santosa Hospital Bandung Central Inpatient Installation.